2017
DOI: 10.22159/ajpcr.2017.v10s5.23093
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pharmacist–doctor Communication on Pediatric Antibiotic Prescriptions

Abstract: Objectives: The purpose of the research was to describe drug-related issues and assess the effect of communication between pharmacists and physicians on decreased prescription drug-related problems in pediatric antibiotics. Methods:Intervention was carried out in the form of pharmacist discussing information-related issues about drugs with physicians prescribing antibiotics to pediatric patients. The research sample included 338 prescription sheets on pediatric outpatient use of antibiotics, and a prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Similarly, a previous study in Iran reported that 5.6% of physicians never consulted their colleagues and 48% of them occasionally consulted their colleagues for antibiotic therapy [ 29 ]. Effective communication between pharmacologists and physicians can reduce the barriers to RAP [ 30 , 31 ]. Clinical pharmacologists can provide physicians with accurate information about medications and thereby, help them select the best antibiotics for patients, increase the effectiveness of antibiotic therapy, and promote RAP [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a previous study in Iran reported that 5.6% of physicians never consulted their colleagues and 48% of them occasionally consulted their colleagues for antibiotic therapy [ 29 ]. Effective communication between pharmacologists and physicians can reduce the barriers to RAP [ 30 , 31 ]. Clinical pharmacologists can provide physicians with accurate information about medications and thereby, help them select the best antibiotics for patients, increase the effectiveness of antibiotic therapy, and promote RAP [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA), carbapenem resistant Enterobacteriaceae (CRE) and vancomycin resistant enterococci (VRE) are the common multidrugresistant organisms (MDRO) being spotted frequently within the hospital wards worldwide [6]. Acinetobacter baumannii, Pseudomonas aeruginosa, Escherichia coli and Clostridium difficile are the salient pathogens causing certain nosocomial infections for which irrational antibiotic prescribing is considered one of the major causes [7,8]. In order to rationalize the antimicrobial (antibiotic) practice, an antimicrobial stewardship (AMS) program is considered an effective intervention [9].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge, attitude, educational background, and social demographics of pharmacists have been considered to be the most likely determinants of the quality of antibiotic services [12][13][14][15]. The shift in pharmaceutical services to patient-oriented services has underscored the importance of pharmacist's ability to communicate with other medical staffs to achieve successful therapy [16]. In some countries, appropriate use of antibiotics is encouraged through the implementation of appropriate policies and interventions.…”
Section: Introductionmentioning
confidence: 99%